(untitled) - 1896-1977.; Hawks, Howard; 1895-1956.; MacArthur, Charles; 1891-1957.; Lockhart, Gene; 1904-1991.; Bellamy, Ralph; Lederer, Charles; 1910-1976.; 1893-1964.; Hecht, Ben; et al. (Los Angeles, 2003)
An unscrupulous newspaper editor uses every dirty trick in the book to keep his ace reporter/ex-wife from retiring and remarrying in this twist on The front page.
Cary Grant of film: A biography of the career of Cary Grant, with selections of scenes from his movies highlighting his career.
Keywords: Grant, Cary; 1904-1986.; Drama; United States; Women journalists; Drama; United States; Divorced people; United States; United States; Reporters and reporting; Drama; United States; Man-woman relationships; Drama; Newspaper editors; Drama